APPLICATION OF THE KAHOOT! TO IMPROVE VOCABULARY MASTERY FOR 8th STUDENTS AT SMP N.7 TOULUAAN - Friska Violet Tumbelaka; Nihta V. F. Liando; Tirza A. Kumayas (Program Studi Pendidikan Bahasa Inggris, 2023)
This study raises a problem that occurs in SMP Negeri 7 Touluaan, namely that difficulties experienced by students while learning English, especially vocabulary mastery. As for some students who still have difficulty understanding, reading, and also having difficulty expressing their ideas in English due to a lack of vocabulary mastery. This research was appointed to examine eighth grade students at SMP Negeri 7 Touluaan. This study aims to measure that students who are taught the Kahoot application have a higher vocabulary mastery or not than those who are taught without using the Kahoot application. The research used was a one group pretest-posttest design. The research design of the group pre test and post test design was measured using the pre test carried out before being given the treatment and the post test which was carried out after given treatment. The instrument used is a test. The questions are in the form of multiple choice, matching and essay there are 25 items of various vocabulary questions. The populations in this study were 20 students of class VIII SMP Negeri 7 Touluaan.